An A–π–A′ structural ratiometric fluorescent probe based on benzo[e]indolium for bisulfite and its application in sugar samples and living cells. Issue 83 (22nd August 2016) - Sun, Yue; Li, Ying; Ma, Xiaotao; Duan, Lian
Abstract : An A–π–A′ structural ratiometric fluorescent probe1 bearing a benzo[ e ]indolium moiety was developed for the detection of HSO3 − in PBS buffer solution. Abstract : An A–π–A′ structural ratiometric fluorescent probe1 bearing a benzo[ e ]indolium moiety was developed for the detection of HSO3 − in PBS buffer solution. HSO3 − was expected to react with probe1 via a Michael addition reaction, causing dramatic changes in its emission spectrum (from 578 nm to 466 nm) and an obvious color change from orange red to blue which could be observed by the naked eye. The reaction could be complete in 30 seconds in the sensing system, and displayed a high selectivity and sensitivity for HSO3 − with a detection limit of 15 nM. The practical value of the probe was confirmed for application to detect the level of HSO3 − in sugar samples with good recovery and in living cells.